A biomechanical analysis of pipe spike motion for elite male volleyball players in official games - Masumura, M.; Quispe Marquez, W.; Endo, T.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to three-dimensionally analyze and compare the pipe spike motion for elite volleyball players and obtain insights into its techniques. The front and pipe spike motions of players of Japan, Brazil and Bulgaria were videotaped during four official games of the Volleyball World Cup 2007 with two high-speed video cameras to obtain three-dimensional coordinates of the body segments. The angles and angular velocities of the upper torso, shoulders, right elbow and wrist were three-dimensionally calculated. The results were summarized as follows. The CG horizontal velocity for the pipe spike was greater than that for the front spike for all players. In the pipe spike, all players shortened the time from the takeoff to the impact and the backswing time. After the takeoff, GG acutely twisted the trunk backward and maintained that position before twisting forward towards the impact in the pipe spike. GG had larger velocity of the left shoulder from the takeoff to the impact for the pipe spike than for the front spike.